Contrast enhanced ultrasound combined with serology predicts hepatocellular carcinoma recurrence: a retrospective observation cohort study - Tu, Haibin; Feng, Siyi; Chen, Lihong; Huang, Yujie; Zhang, Juzhen; Wu, Xiaoxiong (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is mainly treated by surgery; early recurrence (ER), usually within 2 years, severely affects the surgery outcomes. Corresponding treatment can be adopted if ER can be non-invasively predicted preoperatively. We retrospectively recruited 466 cases and created a noninvasive prediction model called Contrast-enhanced Ultrasound Serological (CEUSS) based on ultrasonographic findings and serological markers; internal validation was also done. CEUSS had better predictive accuracy than other classical tumor grading criteria, tumor lymph node metastasis, Barcelona Clinical Liver Cancer staging, and China Liver Cancer Staging; thus, it deserves further promotion in the clinical field.